2018
DOI: 10.3389/fphys.2018.00731
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Myofilament Contraction Drives Right Ventricular Failure Secondary to Pressure Overload: Model Simulations, Experimental Validation, and Treatment Predictions

Abstract: Introduction: Pulmonary hypertension (PH) causes pressure overload leading to right ventricular failure (RVF). Myocardial structure and myocyte mechanics are altered in RVF but the direct impact of these cellular level factors on organ level function remain unclear. A computational model of the cardiovascular system that integrates cellular function into whole organ function has recently been developed. This model is a useful tool for investigating how changes in myocyte structure and mechanics contribute to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 49 publications
1
10
0
Order By: Relevance
“…The recapitulation of the PAB phenotype in CTL myocytes with ML‐7 treatment, along with a lack of effect of ML‐7 on PAB myocytes, implicates the loss of cMLCK as a factor in the impaired contractility of PAB myocytes. A recent multiscale computation study has shown that impaired myocyte myofilament contractility is the major determinant of RV function in the pressure‐overloaded RV (Philip et al, 2018 ). Our data presented here, together with previous studies showing the importance of myocyte contractility to overall RV function in pressure‐overload and the increased expression level of cMLCK in the right ventricle, make this pathway a very promising target for the treatment of pressure‐overload induced RV hypertrophy and failure.…”
Section: Discussionmentioning
confidence: 99%
“…The recapitulation of the PAB phenotype in CTL myocytes with ML‐7 treatment, along with a lack of effect of ML‐7 on PAB myocytes, implicates the loss of cMLCK as a factor in the impaired contractility of PAB myocytes. A recent multiscale computation study has shown that impaired myocyte myofilament contractility is the major determinant of RV function in the pressure‐overloaded RV (Philip et al, 2018 ). Our data presented here, together with previous studies showing the importance of myocyte contractility to overall RV function in pressure‐overload and the increased expression level of cMLCK in the right ventricle, make this pathway a very promising target for the treatment of pressure‐overload induced RV hypertrophy and failure.…”
Section: Discussionmentioning
confidence: 99%
“…The relative impact of these individual components and their interdependence on RV ventricular function is not fully understood. Computational modeling identified reduced myocyte contractility as an important cause of ventricular dysfunction in RV pressure overload but attributed little dysfunction to myocardial fibrosis [64]. Currently applied cell-based strategies to restore RV function are largely focused on exploiting paracrine effects with little evidence of direct or indirect cardiomyocyte regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Clearly, more study is warranted, as experiments in models of ischemic injury in the LV suggest that cell secretome can actually outperform cell-based strategies in terms of contractile recovery in some circumstances [43]. On the other hand, it remains unknown whether the indirect actions of a cell-free therapy, perhaps in combination with myocardial hypertrophy, will suffice to sustain the RV in the face of elevated afterload longer-term or whether the addition of force-generating units will prove essential to overcome heart failure in RV pressure overload [64].…”
Section: Stem Cell Therapy and Its Potential Role In Rv Failurementioning
confidence: 99%
“…Our recent study using a multiscale computational model of the cardiovascular system suggested that decreased myofilament function plays a key role in the development of RVF (19). Furthermore, model simulations predicted that increased myofilament force after A61603 treatment would preserve RV function despite continued pressure overload (20).…”
Section: H229mentioning
confidence: 98%